Comparative Effects of Ovariectomy and Flutamid on Body-Uterus Weight and Uterine Histology in the Ovariectomized Rat Model( p. 221-6) (Annals of Medical Research, 2021)
None
Keywords: Flutamide, Anti-androgen, Ovariectomy, Uterine histology, Body weight